"EFFECTS OF COVID-19 ON SKIN CONDITION" - Shakirova , A.; Zakirov , T.; Kurmanalieva , A.; Torobekova, S.; Shriyam , B. (EurasianUnionScientists, 2020)
This article provides general information about skin lesions in COVID-19, provides detailed information about the elements of the rash, stages of severity and course. Examples of skin changes during coronavirus infection are given, the most common dermatoses are divided into groups. A skin rash in the presence of this infection can appear in people of any age, and moreover, it can worsen and complicate the course of the primary skin process.